Cityfarm Malaysia / Rahil Azhar - Azhar, Rahil (2021)
CityFarm is one of the newly established companies which developed and manufacture hydroponics system equipment. In this company, it is focusing on the hydroponics system that is produced by the CityFarm to be investigated, identified and analyzed along with their current problem and come out with solutions. Hydroponics system is a new technique for the agricultural that use soil-less culture. Unlike the other cultivated soil agricultural crops which produce by other companies or manufacturer. The problem of their product is high cost technology investment. Generally, Hydroponics system expensive is due to the all technology that is need for the vertical farm to cultivate crops. The LED lights, the irrigation system, the climate control computer and all the equipment that ensures the right climate are all factors that make the building cost of a vertical farm expensive. Aside from that, there a solution to that problem which are do some innovation to improve hydroponics system with a new alternative technique that are eco-friendly, safe and produce healthy food product. So this solution is considered to aid CityFarm in producing very quality product to be provided to their customers in order to sustain their business growth, developments and more achievements ahead.